(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Social networks as a modern form of mass media The article considers social networks as a modern form of mass media. It is reported that the role of social networks in the life of adm is growing. Also, social networks are classified and each type is characterized. They discussed in detail the trends, peculiarities, and characteristics of the media industry. Separate characteristics are given to social media created for business and social networks created to meet the informational requirements of society. In general, it is noted that social networks have become an integral part of the ongoing processes in society